2020
DOI: 10.1186/s13063-020-04620-8
|View full text |Cite
|
Sign up to set email alerts
|

Conducting clinical trials in sub-Saharan Africa: challenges and lessons learned from the Malawi Cryptosporidium study

Abstract: Background: An effective drug to treat cryptosporidial diarrhea in HIV-infected individuals is a global health priority. Promising drugs need to be evaluated in endemic areas which may be challenged by both lack of resources and experience to conduct International Committee of Harmonisation-Good Clinical Practice (ICH-GCP)compliant clinical trials. Methods: We present the challenges and lessons learned in implementing a phase 2A, randomized, double-blind, placebo-controlled trial of clofazimine, in treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 9 publications
(17 reference statements)
2
17
0
Order By: Relevance
“…However, a recent controlled clinical trial to assess the safety and efficacy of clofazimine for the treatment of cryptosporidiosis in this population highlighted the significant challenges with this approach. 23 In addition to the operational complexity of conducting early phase clinical trials in resource-poor settings, 37 safety and efficacy evaluation in the HIV/AIDS cryptosporidiosis patient population is highly confounded by the severe immunocompromised state, presence of multiple diarrheal pathogens, other opportunistic coinfections, concurrent medications, failure of antiretroviral therapy, and high mortality. 38 As a potential alternative to investigating NCEs in HIV/AIDS cryptosporidiosis coinfected patients, a Cryptosporidium CHIM in adult healthy volunteers is considered herein as it offers a scientifically robust path to PoC for novel antiparasitic agents.…”
Section: Challenges In Developing a Novel Antiparasitic Agent To Treat Pediatric Cryptosporidiosismentioning
confidence: 99%
“…However, a recent controlled clinical trial to assess the safety and efficacy of clofazimine for the treatment of cryptosporidiosis in this population highlighted the significant challenges with this approach. 23 In addition to the operational complexity of conducting early phase clinical trials in resource-poor settings, 37 safety and efficacy evaluation in the HIV/AIDS cryptosporidiosis patient population is highly confounded by the severe immunocompromised state, presence of multiple diarrheal pathogens, other opportunistic coinfections, concurrent medications, failure of antiretroviral therapy, and high mortality. 38 As a potential alternative to investigating NCEs in HIV/AIDS cryptosporidiosis coinfected patients, a Cryptosporidium CHIM in adult healthy volunteers is considered herein as it offers a scientifically robust path to PoC for novel antiparasitic agents.…”
Section: Challenges In Developing a Novel Antiparasitic Agent To Treat Pediatric Cryptosporidiosismentioning
confidence: 99%
“…These themes reflect aspects frequently discussed in the literature. However, existing literature addressed these aspects mainly from the perspective of ethics [ 24 , 25 ], ICH-GCP applicability [ 2 , 26 , 27 ], or lessons learned when implementing specific studies in specific regions in SSA [ 28 30 ]. In contrast, our study was transnational and strictly oriented towards associations with CT quality, which could but did not necessarily have to overlap with these perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…This phase 2a randomized, double-blind, placebo-controlled study had two parts: part A had primary outcomes of safety, pharmacokinetics, and reduction in Cryptosporidium oocyst shedding; part B was an open-labeled study comparing the pharmacokinetics of matched HIV-positive individuals without cryptosporidiosis (or diarrhea). The study faced many unexpected challenges with study initiation, population, implementation, and cultural issues [ 39 ▪▪ ], though the sponsors were able to find solutions to successfully reach the endpoint. The study found treatment with CFZ had no significant impact on Cryptosporidium oocyst shedding, diarrheal episodes, stool weight, or consistency scores.…”
Section: Clinical Trial Of Clofazimine and Lessons For Future Proof-of-concept Studiesmentioning
confidence: 99%